Relative Gene Expression Study on Casein Protein and its Regulatory Genes in Mammary Epithelial Cells of Surti Goat - Janmeda, Mamta; Pandya, Gaurav; Ramani, Umed; Brahmkshtri, Balkrushna; Patel, Navin; Kharadi, Vishnu (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This investigation was carried out to study the relative gene expression of casein proteins and its regulatory genes in mammary epithelial  cells of Surti goats at 30 and 90 days interval postpartum. 10 healthy Surti goats were selected from Livestock Research Station, Navsari.  The non-invasive method was used for the isolation of Mammary Epithelial Cells (MEC) from goat milk samples. The relative gene  expression of CSN1S1 (αs1-casein), CSN1S2 (αs2-casein), CSN2 (β-casein), CSN3 (κ-casein) and its regulatory genes C/EBP and STAT5A  genes and KRT14 (epithelial cell marker) gene were studied in MEC. The relative gene expression of CSN1S1, CSN1S2, CSN3 and C/EBP genes were significantly up-regulated with the advancement of lactation at 90 days postpartum. The relative gene expression of CSN2  was highly significant and had a positive correlation with its regulatory genes C/EBP and STAT5A at 30 days and 90 days, respectively.  The relative gene expression of CSN1S2, CSN3, and C/EBP genes was positively correlated with protein percent at 30 days and 90 days  postpartum in Surti goats.
Keywords: Casein proteins; Gene expression; Mammary epithelial cells; Surti goat